The Inhibitory Receptor CLEC12A Regulates PI3K-Akt Signaling to Inhibit Neutrophil Activation and Cytokine Release - Paré, Guillaume; Vitry, Julien; Merchant, Michael L.; Vaillancourt, Myriam; Murru, Andréa; Shen, Yunyun; Elowe, Sabine; Lahoud, Mireille H.; Naccache, Paul H.; McLeish, Kenneth R.; Fernandes, Maria J. (Frontiers in Immunology, 2021)
The myeloid inhibitory C-type lectin receptor CLEC12A limits neutrophil activation, pro-inflammatory pathways and disease in mouse models of inflammatory arthritis by a molecular mechanism that remains poorly understood. We addressed how CLEC12A-mediated inhibitory signaling counteracts activating signaling by cross-linking CLEC12A in human neutrophils. CLEC12A cross-linking induced its translocation to flotillin-rich membrane domains where its ITIM was phosphorylated in a Src-dependent manner. Phosphoproteomic analysis identified candidate signaling molecules regulated by CLEC12A that include MAPKs, phosphoinositol kinases and members of the JAK-STAT pathway. Stimulating neutrophils with uric acid crystals, the etiological agent of gout, drove the hyperphosphorylation of p38 and Akt. Ultimately, CLEC12A regulates uric acid crystal-stimulated release of IL-8 by neutrophils through a p38/PI3K-Akt signaling pathway. In summary this work defines early molecular events that underpin CLEC12A signaling in human neutrophils to modulate cytokine synthesis. Targeting this pathway could be useful therapeutically to dampen inflammation.